HUBUNGAN INDEKS MASSA TUBUH DENGAN LAJU FILTRASI GLOMERULUS PADA MAHASISWA DENGAN OBESITAS DI FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI - Baladraf, Fadel; Surachmanto, Eko E.; Moeis, Emma Sy. (Universitas Sam Ratulangi, 2013)
Abstract. Obesity is the big worldwide healthy problem. Obesity itself is a complex disorder of appetite regulation and energy metabolism are controlled by specific biological factors. Individual with obesity will increase the risk of cardiometabolic syndrome, type-2 diabetes, hypertension, dyslipidemia, coronary heart disease, osteoarthritis, stroke, gallblader disease, obstructive sleep apnea, gastroesophageal reflux disease (GERD), chronic kidney disease, and some kind of cancer (endometrial, breast, and colon). The relationship between obesity and chronic kidney disease (CKD) are mediated through several biological mechanism, including hormonal factors, inflammation, oxidative stress, and endothelial dysfunction.The purpose of this research is to know the relationship between body mass index with glomerular filtration rate. This research uses analytic methods to observational cross-sectional stdy design. Data collected from measurements of weight and height, plasma creatinine and by using the Cockroft-Gault formula.Result from the study conducted on 29 people sample consisted of 18 men and 11 women, by using the pearson correlation test can be seen a strong correlation between body mass index with glomerular filtration rate with p=0,000 (p<0,01). Conclusion: body mass index has a relationship (correlation) or significantly stronger with glomerular filtration rate Key word: obesity, glomerular filtration rate, chronic kidney disease (CKD)Â Abstrak.Obesitas merupakan masalah kesehatan di seluruh dunia. Obesitas sendiri merupakan suatu kelainan kompleks pengaturan nafsu makan dan metabolisme energi yang dikendalikan oleh beberapa faktor biologik spesifik. Individu dengan obesitas akan mengalami peningkatan risiko Cardiometabolic syndrome, Diabetes tipe-2, hipertensi, dislipidemia, Penyakit jantung koroner, osteoarthritis, stroke, Penyakit kandung empedu, Obstructive sleep apnea, Gastroesophageal reflux disease (GERD), Penyakit ginjal kronik dan Beberapa kanker (endometrium, payudara, dan usus besar). Hubungan antara obesitas dan penyakit ginjal kronik (PGK) dimediasi melalui beberapa mekanisme biologis, termasuk faktor hormonal, peradangan, stres oksidatif, dan disfungsi endotel.Tujuan penelitian ini adalah mengetahui hubungan antara indeks massa tubuh dengan laju filtrasi glomerulus pada orang dengan obesitas. Metode penelitian bersifat analitik observasional dengan rancangan studi potong lintang.Data diperoleh dari pengukuran berat badan dan tinggi badan, kreatinin plasma dan dengan menggunakan formula Cockroft-Gault.Dari penelitian yang dilakukan pada 29 orang sampel yang terdiri dari 18 laki-laki dan 11 perempuan dengan menggunakan uji pearson correlation dapat dilihat adanya hubungan yang kuat antara indeks massa tubuh dengan laju filtrasi glomerulus dengan nilai p=0.000 (p<0,01). Simpulan: indeks massa tubuh mempunyai hubungan (korelasi) kuat atau signifikan dengan laju filtrasi glomerulus Kata kunci: obesitas, laju filtrasi glomerulus, penyakit ginjal kronis (PGK).